Triggers for solid malignancies diagnosis in patients with rheumatoid arthritis - Aoki, Akiko; Kobayashi, Hiroshi (Clinical Rheumatology and Related Research, 2023)
Objective: In recent years, malignancies have become the leading cause of death among rheumatoid arthritis（RA）patients. Although blood test and urinalysis are regularly performed in rheumatology outpatient clinics, malignancies may still be found in an advanced stage. We analyzed the clinical information of RA patients with solid tumors and summarized the triggers of detection.Subjects and Methods: A single-center, retrospective, observational study. Subjects were 41 RA patients（33 women; 80%）, 48 cancers, who visited our department between April 2011 and June 2023 and attended our clinic for more than 6 months, and who were diagnosed with solid malignancies（cancers）after RA diagnosis. We collected information on age at cancer diagnosis, type of cancer, triggers of detection, duration of RA, and RA treatment at and after cancer diagnosis.Results: The organs in which cancer occurred were breast, lung, colon, uterus, stomach, skin, prostate, pancreas, and others, in that order. the mean age at RA diagnosis was 54.1 years, the mean age at cancer diagnosis was 67.5 years, and the median duration of RA disease before cancer diagnosis was 9.0 years. The most common reason for cancer detection was self-examination for breast cancer, while lung and colorectal cancers were often detected during outpatient or inpatient examinations. Regarding RA treatment, methotrexate（MTX）and TNF inhibitors were often discontinued after cancer diagnosis, and the use of glucocorticoids（GC）was increasing.Conclusion: It was found that early detection of cancers is difficult to be achieved only by regular examinations.